1968
DOI: 10.1002/macp.1968.021160120
|View full text |Cite
|
Sign up to set email alerts
|

Segmental exchange polyacetal‐polyether in the cationic copolymerization of trioxane with dioxolane catalyzed by BF3 in the presence of polyethers

Abstract: ST. PENCZEK, J. FEJGIN, W. SADOWSKA, and M. TOMASZEWICZ spezhchen Oberflachen (ca. 25 m2/g). Polymerisationsansatze mit Polyathern sind selbst bei einem Gehalt von 60 Gew.-% an festem Copolymeren noch fliissig. Eine monomolekulare Schicht von Polyathern (z. T. als Blockcopolymeres, z. T. nur adsorbiert) auf der Oberflache der Polyacetal-Partikel scheint auszureichen, urn die beschriebenen Phlnomene hervorzurufen. Diese Schicht verhindert das Agglomerieren der Polyacetal-Partikel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…[31][32][33] The ring-opening copolymerization of TOX can be initiated by Lewis acid such as BF 3 O(Et) 2 , TiCl 4,34 and CH 3 COClO 4 . 35 Penczek and coworkers 36 studied the solution copolymerization of TOX and a small amount of DOX initiated by BF 3 O(n-Bu) 2 and found that the unstable fraction content of the copolymer increased with increasing conversion, indicative of a higher reactivity of DOX than that of TOX toward the copolymerization.…”
Section: Introductionmentioning
confidence: 98%
“…[31][32][33] The ring-opening copolymerization of TOX can be initiated by Lewis acid such as BF 3 O(Et) 2 , TiCl 4,34 and CH 3 COClO 4 . 35 Penczek and coworkers 36 studied the solution copolymerization of TOX and a small amount of DOX initiated by BF 3 O(n-Bu) 2 and found that the unstable fraction content of the copolymer increased with increasing conversion, indicative of a higher reactivity of DOX than that of TOX toward the copolymerization.…”
Section: Introductionmentioning
confidence: 98%
“…In 1968, Penczek et al reported for the first time on the cationic ring opening copolymerization of 1,3,5-trioxane and 1,3-dioxolane, leading to microspheres. 10 Then, direct synthesis of polyester particles during the polymerization of heterocyclic monomers was patented in the early 1970s. 11 Subsequent papers on the ionic and/or pseudoionic dispersion polymerization were published only very recently.…”
Section: Introductionmentioning
confidence: 99%
“…The conditions allowing us to obtain uniform latexes and microspheres in radical polymerization are well defined. On the other hand, the knowledge of ionic and/or pseudoionic dispersion polymerization is very limited. In 1968, Penczek et al reported for the first time on the cationic ring opening copolymerization of 1,3,5-trioxane and 1,3-dioxolane, leading to microspheres . Then, direct synthesis of polyester particles during the polymerization of heterocyclic monomers was patented in the early 1970s .…”
Section: Introductionmentioning
confidence: 99%
“…Chain transfer to residual water can also take place and justifies the experimentally observed hydroxyl end groups, whereas transfer to polymer (transacetalization) can generate macrocycles when it occurs intrachain or lead to random redistribution of sequences (scrambling) when it occurs interchain, , the latter process becoming particularly critical for the thermal stability of the final product in the case of copolymerization.…”
Section: Introductionmentioning
confidence: 73%